Globalization: An Overview of Its Main Characteristics and Types, and an Exploration of Its Impacts on Individuals, Firms, and Nations - Naeimah Alkharafi; Mariam Alsabah (Economies)
This paper presents a review of globalization by examining its main characteristics, types, and the advantages and disadvantages associated with each type with regard to people, firms, and nations. It synthesizes the literature and provides a structured analysis of the multifaceted impacts of globalization. The review combines the theoretical constructs of globalization characteristics and types, with empirical observations of the contributions and challenges of each type of globalization—based on multiple levels of an analysis—including micro, meso, and macro. Each type of globalization is analyzed to identify how it contributes to economic growth, cultural exchange, political cooperation, technological advancement, and environmental collaboration, while also presenting significant challenges, such as inequality, cultural homogenization, political dependency, digital divide, and ecological degradation. Understanding the multidimensional nature of globalization allows policymakers, business leaders, and individuals to navigate its complexities more effectively, while recognizing both the opportunities and risks. Although much of the literature examined globalization through a single lens, this paper offers an integrative and comparative perspective across the various dimensions. By categorizing the impacts into various levels according to type, it contributes to a more comprehensive and nuanced understanding of globalization.